The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fnins.2019.00708
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of CT Guided Pulsed Radiofrequency Treatment for Trigeminal Postherpetic Neuralgia

Abstract: Objectives Trigeminal postherpetic neuralgia (TPHN) often presents with moderate to severe pain, hyperalgesia, and allodynia. Conventional analgesic treatments are poorly effective, which seriously affects the quality of life. This retrospective study aimed to evaluate the efficacy of pulsed radiofrequency (PRF) for the treatment of TPHN. Methods A total of 90 TPHN patients were selected between January 2014 and December 2016 in the Department of Pain Management, Shengj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…PRF can block pain transmission by interrupting signals in unmyelinated C fibers and myelinated A-delta fibers without influencing myelinated A-alpha and A-beta fibers. 31 Moreover, PRF appears to change c-fos mRNA expression in the dorsal horn of spinal cord. 32 In our NMA, PRF was highly effective for pain reduction in PHN patients at all time points compared among all the analyzed interventions.…”
Section: Discussionmentioning
confidence: 99%
“…PRF can block pain transmission by interrupting signals in unmyelinated C fibers and myelinated A-delta fibers without influencing myelinated A-alpha and A-beta fibers. 31 Moreover, PRF appears to change c-fos mRNA expression in the dorsal horn of spinal cord. 32 In our NMA, PRF was highly effective for pain reduction in PHN patients at all time points compared among all the analyzed interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly patients are prone to postherpetic neuralgia (PHN) following VZV-induced herpes zoster [ 25 ]. Thoracic, cervical, and trigeminal nerves are commonly involved in PHN [ 26 , 27 ], which may cause anxiety, depression, sleep disorders, and other complications. As a result, the life quality of elderly patients was seriously reduced [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is dispensed in a short interval of 20 ms and then intermittently for 480 ms so that the generated heat is diffused and the temperature produced does not exceed 42 • C. Therefore, PRF only produces persistent neuromodulation and does not produce a destructive effect as RFT. Recent studies have found that PRF can produce neuromodulation and relieve trigeminal PHN (Ding et al, 2019). It has been found that PRF can inhibit the nociceptive-induced release of excitatory neurotransmitters (Huang et al, 2016), reduce the expression of calcitonin gene-related peptide (CGRP) in DRG (Ren et al, 2018), inhibit the expression of P2 × 3 receptor in DRG and spinal dorsal horn (Fu et al, 2019), and reduce the expression of peripheral of pro-inflammatory cytokines (TNF-α and IL-6) and β-Catenin in spinal cord (Vallejo et al, 2013;Jiang et al, 2019); At the same time, PRF can up-regulate GDNF transcription and translation (Jia et al, 2016;Hailong et al, 2018), up-regulate GABAB-R1, Na/K ATPase and 5-HT3r gene expression (Vallejo et al, 2013), increase histone acetylation and KCC2 expression by modifying KCC2 and partially restored GABA synaptic function (Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%